Case Report: Unmasked Inherited Dysfibrinogenemia After Everolimus Therapy - Merkulova, Alona A.; Mitchell, Steven C.; Merkulov, Sergei; Wolberg, Alisa S.; Neerman-Arbez, Marguerite; Schmaier, Alvin H. (Frontiers in Medicine, 2020)
A previously hemostatically asymptomatic patient with common variable hypogammaglobulinemia was given everolimus to prevent growth of her liver. Within several months, the patient developed a severe bleeding disorder. The bleeding was due to fibrin polymerization defect that upon sequencing was shown to be dysfibrinogenemia Krakow III. Elimination of the mTor inhibitor ameliorated the clinical bleeding state.